(3QSGdI aj CSeGA GdCSO hcfGgs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bOQ eGTGA eeG SJQ hSGA bGd GdedJLi Edi MQa Gddg GdTQja GdMSf Hf eMeO Hf GdMSf GdUGZGfi gPG eNJUQ LeYJg ai CSGei GdCSO hcfGg eQJHI Ydi MQha GdeYLe s
(3BNQgG (B:s
(3hdbO HcjJ Ydi GdQGb HGOeY CSakG Ydi Cf GdHcG dGjfaY hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hYdi Bgdg hUMHg hSde JSdjekG cKjQkG Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds